The community in business: strategic relationship between companies and environment and marketing - Fernando Juárez Acosta (Universidad de San Buenaventura, 2014)
Community language is not unrelated to companies (Chaston & Mangles, 2001), which define their activities as a benefit for community through sales of products or services. They also use in the social responsibility activities (Kakabadse, Rozuel, & Lee-Davies, 2005; Korhonen, 2002) in the community-corporation involvement (Burke, 1999) that adds value to the latter ones (Rochlin, & Christoffer, 2000, p.1) in regards to the social marketing (Whitcombe, 2009) aiming to the elimination of barriers that hamper the implementation of social programs (McKenzie-Mohr, 2000a, 2000b), or, with a strategic view, in regards to the shared value that benefits community and companies at the same time (Porter & Kramer, 2011). There are, of course, many other ways to incorporate such language in companies.